Content Validity of Defining Characteristics of the Nursing Diagnosis of "Spiritual Distress" - Fateme Eshghi; Azam Shirinabadi Farahani; Armin Zareiyan (Mashhad University of Medical Sciences, 2023)
Background: Spiritual distress negatively affects well-being, and its effects are much stronger and more permanent than the positive aspects of spirituality. Since spiritual distress has destructive effects, the introduction and validation of defining characteristics, which are most likely expressive of spiritual distress in the client, can be applied in the daily use of this nursing diagnosis for the quick identification of individuals with spiritual distress, designing targeted and culture-based nursing care, and cost reduction.Aim: The present study was performed with aim to assess the content validity of the defining characteristics of nursing diagnosis of "spiritual distress".Method: This methodological study was performed based on the six steps of Fehring's diagnostic content validity model. A total of 40 nursing experts participated in the study to validate 74 defining characteristics. Descriptive statistics and Fehring's diagnostic content validity model were used for data analysis.Results: Contents validity of 74 defining characteristics was assessed. Six defining characteristics were identified as primary that four were introduced by North American Nursing Diagnosis Association (NANDA), four were considered as irrelevant and 64 were identified as secondary that 29 were introduced by NANDA. The total score of diagnostic content validity was 0.68.Implications for Practice: Validation and identification of defining characteristics as representative of nursing diagnosis of spiritual distress can be effectively applied to help quick and correct identification and provide targeted and optimal nursing care.